2016
DOI: 10.1038/mt.2015.212
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Map of CNS Transduction by Eight Recombinant Adeno-associated Virus Serotypes Upon Cerebrospinal Fluid Administration in Pigs

Abstract: Cerebrospinal fluid administration of recombinant adeno-associated viral (rAAV) vectors has been demonstrated to be effective in delivering therapeutic genes to the central nervous system (CNS) in different disease animal models. However, a quantitative and qualitative analysis of transduction patterns of the most promising rAAV serotypes for brain targeting in large animal models is missing. Here, we characterize distribution, transduction efficiency, and cellular targeting of rAAV serotypes 1, 2, 5, 7, 9, rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…IT delivery has the added benefits of reduced targeting of virus to peripheral organs and avoidance of AAV9-neutralizing antibodies in the blood as compared to systemic delivery. 17 , 18 , 19 , 37 The biodistribution of AAV9 in small and large animals has been validated across multiple labs, 19 , 21 , 38 and here we show that the distribution of gigaxonin expression 1 year post-IT injection of AAV9/JeT-GAN in mice agrees with that data. Further, IT delivery of vector is a minimally invasive route of injection and is scalable to humans.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…IT delivery has the added benefits of reduced targeting of virus to peripheral organs and avoidance of AAV9-neutralizing antibodies in the blood as compared to systemic delivery. 17 , 18 , 19 , 37 The biodistribution of AAV9 in small and large animals has been validated across multiple labs, 19 , 21 , 38 and here we show that the distribution of gigaxonin expression 1 year post-IT injection of AAV9/JeT-GAN in mice agrees with that data. Further, IT delivery of vector is a minimally invasive route of injection and is scalable to humans.…”
Section: Discussionsupporting
confidence: 86%
“…Studies of IT delivery of AAV9 in mice and NHPs show a dose response wherein a higher dose correlated to a higher percentage of transduced cells. 20 , 21 , 38 Notably, none of these studies reached a saturating dose of AAV9, and we have shown that our construct design for GAN is unlikely to introduce overexpression-related toxicity. Together, these data support the safety of increasing the dose administered in patients in order to increase the percent of transduced cells in the spinal cord and brain and maximize the therapeutic benefit.…”
Section: Discussionmentioning
confidence: 88%
“…[ 28 ]. Due to the lack of specific data, every time point can provide important insights, and the 30 days old model has recently been used to describe new techniques [ 17 , 29 ] and characterize new gene therapy patterns [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal (IT) or IV administration of rAAV9 is a less invasive systemic delivery method that efficiently transduces genes into multiple tissues, including the CNS. Delivery of various rAAV serotypes to CNS lesions via CSF administration in a large animal has been studied [6365]. These studies show that rAAV9 has high transduction efficiency in widespread CNS lesions including the spinal cord.…”
Section: Pre-clinical Study Of Gene Therapy For Mpsmentioning
confidence: 99%